Diagnosis of liver trichinellosis using magnetic resonance imaging (clinical case report) - Anastasiia-Violetta Matsiievska; Volodymyr Bogomaz (Bogomolets National Medical University, 2022)
the prevalence of helminthiasis in the world remains quite high and most of them involve the hepatobiliary system. Considering the specificity of treatment plans, timely nosological diagnosis of liver lesions is extremely important. The amount of research on this topic is currently very limited. The aim of the work was an identifying of MRI capability in the diagnosis of liver trichinellosis to ensure timely recognition and differential diagnostic of the disease. Nonspecific focal changes in the liver parenchyma were found in a 30-year-old woman without any oncological history during ultrasound examination. It is known about her trips to Asian countries several years ago. Clinical manifestations that are specific to trichinellosis were not found in the patient. Examination of the patient's abdominal organs on magnetic resonance imaging with 3.0 T field induction (T1-WI, T2-WI, DWI-sequences, bolus dynamic contrast enhancement) showed the presence of a sign of a "curved tunnel" in the liver parenchyma. Serological tests that confirmed the diagnosis of trichinellosis were performed in Great Britain. The patient has no other clinical and laboratory signs of pathology and she still be under clinical observation. According to the data of the literature and our observation, the sign of the "curved tunnel" on magnetic resonance imaging is a sensitive criterion for the diagnosis of trichinellosis of the liver. In the case of clinical and diagnostic uncertainty of local changes in the liver parenchyma after basic radiological studies (sonography, computer tomography) and in the presence of risk factors for helminthiasis, despite the high cost, it is advisable to include MRI of the liver in the patient examination algorithm to speed up the duration and ensure the accuracy of the diagnosis.